Climate Change and Livelihood Issues: Some Empirical Evidences - Anshuman Upadhyay (JOURNAL OF INDUSTRIAL RELATIONSHIP CORPORATE GOVERNANCE AND MANAGEMENT EXPLORER, 2023)
Climate Change has now being acceptable and perceptible phenomena amongst people residing in rural areas. One of the greatest impacts is disruption of livelihoods, especially of rural communities because they have large dependency upon climate sensitive natural resources for their livelihood. In the present study, four villages from two tehsils of Sikar District, Rajasthan have been studied to ascertain the livelihood vulnerabilities of households. The study is based upon indicator approach and the vulnerability has been calculated following the IPCC Third Assessment Report’s considerations about vulnerability. The villages and the households have been selected through random sampling technique and a questionnaire was administered amongst the selected household to find out various socio-economic parameters. Data collected have been analyzed using Principal Component analysis, by assigning weights to each indicator, which were further aggregated in to exposure, sensitivity and adaptive capacity indices. Livelihood vulnerability index has been calculated for the villages and tehsils. Adaptation Options being followed by households have also been studied .Focus group discussions were also carried out in the communities and the perceptions gathered were compiled. The empirical findings have been analyzed and the level of vulnerability between two tehsils has been compared. The results have been discussed and suggestions have been given for wider policy implications. Key words: Climate Change, Livelihood, Indicator approach, Vulnerability, Adaptation.